A capacidade funcional e o nível de aptidão física em um grupo de idosos para realização de atividades de vida diária em um grupo de idosos - Vilas Boas, Regilane de Fátima (2005)
Population aging is the most important demographic change that has occurred in many countries around the world and represents a challenge for the 21st century. This study aimed to investigate and measure the functional capacity and the level of physical fitness to perform daily tasks in a group of elderly residents in the municipality of Diamantina, MG. The studied group consisted of forty-eight elderly people from the Family Health Program "Viver Melhor", aged between 60 and 69 years. These participants were submitted to a screening, in which they were selected according to the inclusion criteria. Afterwards, they were subjected to a battery of physical fitness assessment tests for the elderly, which meticulously gather tests that measure the various areas of physical fitness, bringing normative results tables, and that simulate some of the most important activities of daily living in the daily lives of men and women. The battery of tests incorporated the measurement of strength, flexibility, cardiorespiratory resistance, motor skills and body composition. The results obtained showed that most of the individuals evaluated were overweight, had a waist-to-hip ratio with levels characterized as high risk for the occurrence of coronary disease and reduced functional capacity and physical fitness.